Enhancing Academic Competence for Students with Disabilities: A School Review of the Post School Transition Program - Gunarhadi Gunarhadi; Mahardika Supratiwi; Joko Yuwono; Herry Widyastono; Hermawan Hermawan; Dewi Sri Rejeki; Mohd Hanafi Mohd Yasin (International Journal of Pedagogy and Teacher Education, 2021)
High school leavers generally expect to be accepted into higher education. For graduate students with disabilities (SWD), however, entering college remains an exception. This study aims to identify the academic barriers to learning and the strategic preparation needed for college admission. The study was conducted in 12 special education high schools in Central Java, Indonesia. A questionnaire and focus group discussion with the school teachers were employed to collect data on the transition programme activities of the respective schools. The questionnaire was self-reported by the school staff, who consisted of headmasters, teachers, and administrators, while the interview was used to elicit the academic barriers that students with disabilities encounter within their respective special schools. The data were analysed using both descriptive quantitative and qualitative measures. It was found that 1) students with disabilities interfere with both internal and external barriers to learning; 2) policies on the right to education provide meaningful assistance in the university enrolment of students with disabilities; and 3) the modified curriculum and instructional strategies are best employed with a variety of extra curricular activities. The research concludes that academic post school transition makes a major contribution to college admission for those with mild disabilities.